(untitled) (IAHS Medical Journal, 2024)
Background: Current inguinal hernia operations are generally based on anatomical considerations. Failures of such operations to some extents are due to lack of consideration of physiological aspects. Many patients with inguinal hernia are cured because of current techniques of operation, though factors that are said to prevent hernia formation are not restored. Therefore, the surgical physiology of inguinal canal needs to be reconsidered. In the year 2001, Mohan P Desarda first described a physiological repair technique of inguinal hernia, which is practiced in many centers with significantly positive outcome. To evaluate the post-operative outcome of Desarda technique versus Lichtenstein mesh hernioplasty in inguinal hernia repair, this research has performed. Materials and methods: This Quasi experimental study was carried out in Surgery Department of Chittagong Medical College Hospital, during December 2017 to January 2019. A total of 100 patients with inguinal hernia underwent surgery were included in this study. Samples were selected by convenient technique. Among them 50 patients were selected for Desarda Technique was considered as group I and the rest 50 patients were selected for Lichtenstein Mesh Hernioplasty was considered as group II. Statistical analysis of the results was obtained by using window-based computer software devised with Statistical Packages for Social Sciences (SPSS-22). Results: The proposed sample size was 50 in each group. The study group included male patient above 18 years of age undergoing Desarda Technique and Lichtenstein Mesh Hernioplasty for inguinal hernia repair. The mean age was 43.14±14.44 years in group I and 48.33±12.63 years in group II. Indirect hernia was found 37(74.0%) and 28(56.0%) in group I and group II respectively. The mean 3rd POD pain (NPRS) was 4.44±0.97 in group I and 5.52±0.71 in group II. The mean 10th POD pain Numeric Pain Rating Scale (NPRS) was 0.76±1.02 in group I and 2.62±1.21 in group II. The mean 1 month pain (NPRS) was 0.08±0.27 in group I and 0.72±0.7 in group II. The mean 3rd month pain (NPRS) was 0.02±0.14 in group I and 0.34±0.48 in group II. The mean 6th month pain (NPRS) was 0±0 in group I and 0.2±0.45 in group II. Pain (NPRS) was significantly (p<0.05) higher in group II in 3rd POD and all subsequent follow-up. Seroma was found 5(10.0%) at 10th POD in group I and 5(10.0%) in group II. The difference was statistically not significant (p>0.05) between two groups. Wound infection found 2(4.0%) in 3rd POD in group Iand 5(10.0%) in group II. Wound infection didn’t develop in subsequent follow-up in group I but in group II, 1(2.0%) found in 10th POD, 1(2.0%) in 1 month, 1(2.0%) in 3rd month, 1(2.0%) in 6th month. The difference was not significant (p>0.05) between two groups. Recurrence was not observed in either group during this study period. Conclusion: Desarda technique of inguinal hernia repair in our set up is useful with comparable results to Lichtenstein hernioplasty. IAHS Medical Journal Vol 7(1), June 2024; 91-96